Dinamika Kesetiaan Pada Kaum Gay - Wedhanti, Putu Hening; Fridari, I Gusti Ayu Diah (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2014)
Homosexual is an interest in feeling or in erotic, both are in predominant or exclusiveness against individuals who has a similarity in sexes violent or without involves interaction physical, while gay is term to mention man who likes fellow man as partners sexual, and have interest both in feeling or erotic, both in dominant and exclusive and also with or without any relation physical (Putri, 2013) Faithfulness is a form of behaviors that performed recurrently that will eventually become a permanent nature. Directed toward your faithfulness also means that individual in relationship was able to rely to keep commitments together, which has agreed by Cloud&Townsand (in Sari, 2008). The aim of this research is to find out the dynamics of faithfulness to gay. This research using qualitative methods by case study approach to describe the dynamics of faithfulness in gay relationship. To collecting data in this research used interview technique and used 4 subject. This research used thematic coding for analyzing data. The result of this study suggest that in a world of a gay, most individuals within it are the people who run the principle of free life, where they hang out and behaving freely without any rules that tie it. Generally the respondents in this study say that faithfulness is crucial and absolutely there are in relationship but not all gay capable of running commitment to remain faithful. Keywords: Homosexual, Gay, Faithfulness, Qualitatife, Case study